2011
DOI: 10.1016/j.foodchem.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids and antioxidant capacities from Canarium odontophyllum Miq. fruit

Abstract: a b s t r a c tCarotenoids were isolated and identified from peel, pulp and seed fractions of Canarium odontophyllum Miq., and their antioxidant capacities were evaluated. all-trans-b-carotene was present in a large amount in peel (69.5 ± 1.0 mg/kg), followed by pulp (31.1 ± 0.76 mg/kg) and seed (15.1 ± 3.0 mg/kg). Additionally, 15-cis-b-carotene, 9-cis-b-carotene and 13-cis-b-carotenes were also major contributors to carotenoid contents in peel, pulp and seed fractions. Pulp exhibited excellent b-carotene ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
52
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 22 publications
10
52
0
2
Order By: Relevance
“…Hence, this is clearly explained why the flesh (outer part) have more carotenoid contents as compared to its seed (Table 1). Previously, carotenoids profiles of peel, pulp and seed of the fruit and their related antioxidant capacities showed that the peel and pulp was enriched with all-trans-β-carotene, when compared with the seed part of C. odontophyllum [28], which also supported the findings of the present study.…”
Section: Total Carotenoid Contentsupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, this is clearly explained why the flesh (outer part) have more carotenoid contents as compared to its seed (Table 1). Previously, carotenoids profiles of peel, pulp and seed of the fruit and their related antioxidant capacities showed that the peel and pulp was enriched with all-trans-β-carotene, when compared with the seed part of C. odontophyllum [28], which also supported the findings of the present study.…”
Section: Total Carotenoid Contentsupporting
confidence: 92%
“…The total phenolic content of C. odontophyllum was higher in the flesh than in the seed ( Table 1). The results of this study are in line with those of previous studies which also reported that the edible parts of C. odontophyllum (i.e peel and pulp) exhibit high phenolic content as compared to the seed part of the fruit [21,22]. Ellagic acid and vanilic acid are among the phenolic acids that are reported to be present in C. odontophyllum [23].…”
Section: Total Phenolic Contentsupporting
confidence: 91%
See 1 more Smart Citation
“…The presence of phenolic compounds, such as flavonoids, phenolic acids, and anthocyanins, in addition to those already known, such as vitamins C and E, and carotenoids, contributes to the beneficial effects of these foods (Silva et al 2004;Ajaikumar et al 2005). In recent years, there is a growing interest in determining the total phenolic contents and antioxidant capacities of vegetables and fruits (Ayala-Zavalaa et al 2004;Zheng et al 2007;Çelik et al 2008;Rui et al 2011;Prasad et al 2011). Phenolic compounds content can be influenced by the factors such as maturity, species, type of cultivation, geographic origin, level of growth, harvest conditions and storage process .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the fruit was also found to be a very good source for high energy, protein and fat, as well as minerals such as calcium, magnesium and phosphorus (Azlan et al, 2009). In addition, it was reported that the peel, pulp and kernel of C. odontophyllum also showed high antioxidant content (Prasad et al, 2011) as well as antifungal effects against Candida glabrata . Dabai seed had high anticholinesterase activity (Hassan, 2014).…”
Section: Introductionmentioning
confidence: 99%